The Indonesian Independent Learning Regulation and Students Economic Proficiencies - Muhammad Hidayat (Jurnal Pendidikan Ekonomi, 2024)
This research is intended to investigate the effect of the implementation of the independent campus learning program in Indonesia, which is intended to provide off-campus learning rights for students to study things other than the field of science they are engaged in both in other study programs and in other institutions outside the campus. is expected to provide additional knowledge and insight so that it will provide benefits for students after graduating from university, the effect of implementing the program is seen from the difference in economic proficiency scores for economics students who take part in the program and those who do not take part in the program, the measure used in viewing proficiency scores is Hansen's proficiency measurement model. This study involved 200 students who were divided into two groups, namely group one were students who took part in the program while group two were students who did not take part in the program. The results of this study indicated that there was a significant difference in proficiency scores for students who took part in the program compared to students who did not take part in the program.